Penerapan Media Pembelajaran Berbasis Video Animasi Pada Materi Laju Reaksi dan Faktor-faktor Yang mempengaruhi Laju Reaksi - Adelia Mewengkang; Meytij J Rampe; Septiany Ch Palilingan (Chemistry Department, Universitas Negeri Manado, 2020)
The Purpose the Study Determine The Average Students Learning on Animation Video Media. The research is a experimental class XI MIA with one class experimental and one class control each class consisting of 30 students. Data the results a average 86,40 for experimental average 53,50 for class control. This matter average class experimental higher then class control.